Emission performance assessment of in-use diesel-driven cars. Issue 1 (1st October 2022) - Pandey, Abhinav; Mishra, Rajeev Kumar; Pandey, Govind
Abstract: The overall fleet of light-duty vehicles in most of the developing countries is characterized by various manufacturers of diesel-driven passenger cars. There is a need of a thorough assessment of the actual conformance levels of such cars towards in-use emission norms, particularly the diesel-driven ones, in consideration of their high proportion in the overall privately-owned passenger cars fleet. In this context, the study conducted on 400 number of light-duty diesel cars reported that the compliance levels for BS (Bharat Stage) III diesel cars are better than that for BS IV, although not varying significantly (90 % in case of former vs. 80 %). Based on the findings, there is a need to include vehicle-related parameters during emission certification, such as, age, mileage and maintenance records along with emission measurements while deciding upon phasing-out of vehicles rather only based upon age (10 years of allowable registration life for diesel cars in the state of Delhi). Based on the results, the inclusion of mass emission-based testing in the overall transport emission assessment and reduction policy of the developing countries is highly recommended.